Application analysis of image recognition based on multiple intelligence algorithm. (May 2020) - Jiang, Jiyue; Wu, Hao; Cui, Yang; Cai, Yijia; Yu, Chenglong; Zhong, Ruitao
Abstract: Image recognition technology based on artificial intelligence algorithm has entered a rapid development stage. According to the development and research status at home and abroad, we can see that PCA, ANN, SVN and other technologies can effectively realize the recognition and generation of images, especially the extraction and prediction of face features, classification and recognition. The analysis and application of the generation countermeasure network (GAN) technology is mainly embodied in the realization of the generation and analysis of handwritten numbers, and the accurate prediction of the promotion and application of SVM technology, as well as the comprehensive and accurate analysis of the generation effect. This paper mainly studies the comparative analysis and application of human face database (ORL) through the relevant data. By extracting 50 face samples, 500 face images are produced for recognition analysis and application.